PLAN DE MARKETING PARA LA EMPRESA, “CELL-COMP” DE REPARACIÓN DE EQUIPOS INFORMÁTICOS, DEL CANTÓN NANGARITZA PROVINCIA DE ZAMORA CHINCHIPE - CASTILLO QUEZADA, MERCY JACKELINE (2019)
The aim of the research project is to work out a marketing plan, for Computer Equipment Repair for "Cell -Comp" Enterprise in Nangaritza town Zamora Chinchipe province. Among the specific objectives were established the following: To analyze the current situation of the "Cell-Comp" Enterprise, to carry out a study of internal and external factors using the FODA matrix and develop a marketing plan, for "Cell -Comp" Enterprise in Nangaritza town Zamora Chinchipe province. For the objectives fulfilment this present project has been taken into account the following methods which are:(deductive, inductive, descriptive and synthetic) and techniques (survey, interview and direct observation). 273 surveys were applied for external customers and 3 internal employees of "Cell -Comp" Enterprise. Furthermore, 6 interviews were made of different Enterprise that works in the same economic activity, in addition to making the direct observation to know the events that occur in the enterprise, such as customer service, identify the type of service offered, also see the location or presentation of the products. On the other hand, in the literature review were considered some fundamental theories such as, bibliographic basis, following a logical sequence where I could analyze the current situation of the Cell-Comp Enterprise; in the internal and external part. Consequently, the whole executed process for the realization for the present research project the same that started with the internal analysis of the enterprise that, through the information collected, the internal factor evaluation matrix (MEFI) was prepared, giving as the result is a weighted value of 2.75, which means that the enterprise has a predominance of strengths over weaknesses. Additionally, the evaluation matrix of external factors (MEFE) a weighted value of 2.66 was obtained, thus determining that the external analysis is in favor of the enterprise since it has a predominance of opportunities. Besides that, the PESTE matrix 5 was also used for the political, governmental and legal factors (P); economics and financials (E); socials, cultural and demographics (S); technological and scientific (T); and ecological and environmental (E); thus, those matrices were used in the whole process for the research as a result it gave me the way to elaborate the high impact matrix which are combined and weighted creating some solution strategies, due to, it was carried out for the strategic objectives for the proposal of the marketing plan that go on in pro development of the enterprise. Finally, after having done the corresponding studies as a conclusion and recommendation it had been considered to Juan Carlos Castillo, manager of the enterprise as a later execution that benefit the business development in an efficient and effective way.